Mating traits are phenotypically but not genetically correlated to fitness. (3rd June 2022) - Collet, Julie M; Sztepanacz, Jacqueline L
Abstract: Misalignment between male and female interests over mating creates interlocus sexual conflict that is known to drive the coevolution of reproductive traits. Males and females also share the majority of their genome, which may cause these traits to be genetically covary between the sexes and experience intralocus sexual conflict where beneficial alleles in one sex are costly when expressed in the other. Here, we use a quantitative genetic experiment to test whether intralocus sexual conflict is operating on mating latency and copulation duration in the polyandrous fruit-fly Drosophila serrata . We performed two paternal half-sibling breeding designs in different populations and measured mating latency and copulation duration in males and females, and components of pre- and postcopulatory fitness in both sexes. Our design enabled the estimation of selection on mating latency and copulation duration and the heritabilities, and within-sex and across-sex genetic covariances of these traits. Mating latency and copulation duration were both heritable in males but not in females, and within sex and across-sex genetic correlations among the traits were all small. Despite significant phenotypic correlations between these mating traits and some male and female fitness components, we found no significant genetic covariance between any measured mating behaviors and fitness components, nor between male and female fitness. Our study, therefore, finds little evidence of ongoing intralocus sexual conflict over these traits. One explanation for our result is that these mating traits have been under strong selection, which has exhausted their genetic variation, limiting their ability to respond to ongoing selection. Abstract : Mating behaviors, because they result from an interaction between a male and a female whose reproductive interests may not be aligned, can cause sexual conflict. We studied the genetic architecture of mating latency and copulation duration in Drosophila serrata. Despite phenotypic correlations between mating traits and some male and female fitness components, there was no genetic covariance between those traits. Altogether, our study finds little evidence of ongoing intra-locus sexual conflict over mating traits.